A Model of Effective School Administration in Schools under the Secondary Educational Service Area Office Loei, Nong Bua Lamphu - Channuan, Kritsada; Pangthai , Sasirada; Sonjai, Songdej (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to: 1) examine the current conditions, desirable conditions, and priority needs for effective school administration in schools under the Loei-Nong Bua Lamphu Secondary Educational Service Area Office; 2) develop a model for effective school administration and 3) evaluate the model for effective school administration. The research employed a mixed-methods design conducted in three phases. The research site covered schools under the Loei-Nong Bua Lamphu Secondary Educational Service Area Office. The study participants consisted of 129 school administrators and 211 teachers. The school administrators were elected through purposive sampling. For the teachers, a stratified random sampling technique was employed, using academic clusters (interdisciplinary campuses) as strata. Proportional allocation was applied to each stratum, followed by simple random sampling via a lucky draw method to identify the final participants. Four research instruments were used: 1) questionnaires, 2) interview guides, 3) evaluation forms, and 4) data record forms. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed through content analysis. The findings revealed that: 1) The current conditions of effective school administration were at a moderate level overall, while desirable conditions were at a high level. The priority needs index ranked administrative structure as the top priority. 2) The developed model consisted of six components with 60 indicators. 3) The overall evaluation of the model for effective school administration showed high levels of appropriateness and feasibility.